PENYULUHAN HUKUM TENTANG TRANSFORMASI PELAYANAN PERIZINAN MELALUI MAL PELAYANAN PUBLIK UNTUK MENINGKATKAN KESADARAN HUKUM MASYARAKAT DI KELURAHAN BELLO - Benediktus Peter Lay; Mary Grace Megumi Maran; Agrifin Bernadeth Criemen Lokovettor; Yoachina Da Cunha Fernades; Maria Elvira Suni (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Public service mall (MPP) is one of the policies that has been present in almost all regions of Indonesia and contributes to creating public services including effective and efficient licensing. However, until now, there are still people in Kupang City including Bello Village who do not know the existence of MPP Kupang City and have not utilised the available public service facilities. These conditions reflect two problems, namely (1) lack of knowledge, understanding, and legal awareness of the community regarding the existence of MPP and the types of services provided, and (2) the low level of community participation in utilising various public services available at MPP Kupang City. In response to the problem, the PKM team of the Faculty of Law, Catholic University of Widya Mandira carried out community service regarding the transformation of licensing services through MPP. The method applied is in the form of legal counselling combined with interactive discussion. In the activity, the speakers conveyed material about the legal basis of the implementation of MPP, definition, purpose, benefits of MPP, MPP organiser in Kupang City, location of MPP Kupang City, MPP service provider Kupang City, implementation of services in MPP, and Agencies that join in the implementation of public services including licensing through MPP Kupang City. The PKM team also emphasised community participation in accessing services through MPP Kupang City including complying with the established procedures and service flows. Through this PKM initiative, the public has gained a better understanding of the services provided through the MPP, including the requirements and necessary documents, and has been encouraged to participate in and make use of the services provided through the MPP.